Inventory control as a strategic differential: a bibliometric analysis through PROKNOW-C - Giacomin, Carina; Gomes, Thiara Cezana; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2021)
This study has as general objective to analyze the bibliographic portfolio found through the ProKnow-C method, which brings relevant articles related to the theme: Inventory control as a strategic differential. The ProKnow-C method is a quantitative analysis of published articles made through filters such as the reading of parts and completeness of the text and the number of citations that appear in Google Scholar, among others. From this study, 16 papers were identified that make up the bibliographic portfolio, where prominent authors were observed in these works, the prominent means of publication, the material that served as the basis for the works, in addition to pointing out the contributions of each one of them.
Keywords: Inventory Management; ProKnow-C; Strategic Differential